Load Carrying and Hydrostatic Performances of Innovative Encapsulated Anchorage System for Unbonded Single Strand - Min Sook Kim; Young Hak Lee (Advances in Civil Engineering)
A new anchorage system is proposed having a circular bearing plate and curvature between the bearing plate and the anchor head to improve stress concentration. A lid with a screw instead of the grouting method is also proposed to prevent moisture penetration. The details of the anchorage device have been chosen to reduce stress concentration based on the finite element analysis. Static load test, load transfer test, and hydrostatic test of fabricated devices were carried out according to ETAG 013 to evaluate the proposed design. As results, the anchorage slip and stabilization satisfied the recommendations of ETAG 013. The maximum load in the load transfer test was at least 1.1 times the ultimate tendon strength. The results of the hydrostatic test showed that the developed anchorage device is watertight to protect against corrosion. As a result of bursting force test, it was confirmed that the proposed anchorage device has more advantages than the conventional rectangular anchorage devices in terms of stress distribution.